Assessment of Healing Forest Potential for Nature-Based Tourism in Bogor Botanical Gardens - Riswan, Arbi Pangestu; Hasibuan, Ratna; Sasongko, Dwi Agus (Journal of Sylva Indonesiana, 2026)
Healing forest activities, such as Bogor Botanical Gardens, have become increasingly popular among urban communities, especially those experiencing stress or seeking peace. Healing forests offer a calming effect on the body, soothe the mind, and create a sense of comfort that can help lower stress levels through relaxation activities immersed in nature (natural healing). This study aimed to identify potential areas suitable for forest-healing activities based on the standards outlined in the SNI 9006:2021. This study uses a mixed-method approach combined with field observations. The collected data were analyzed using a descriptive method. The results showed that one location, Area Six, has a strong potential for Healing Forest activities. Based on on-site analysis, activities that can be carried out in this area include yoga, forest walks, tree-hugging, and simply enjoying natural surroundings.